Balance on social inclusion and environmental justice at the end of the 30 years of the drinking water service concession in the city of Aguascalientes, Mexico - Caldera Ortega, Alex Ricardo; Tagle Zamora, Daniel (Frontiers in Sustainable Cities, 2023)
After three decades since the concession for drinking water and sewerage services was granted to a private company, which eventually became part of the Veolia group in the city of Aguascalientes, Mexico, it is necessary to assess the situation. The local government chose not to renew the contract and, furthermore, opted to remunicipalize the system and its management. This document provides an evaluation from the perspective of political ecology, which focuses on two dimensions: social inclusion and environmental justice. Clearly, the primary outcomes are within the framework of water commodification, where the service operation primarily views users as customers who must pay their fees promptly, while the city's growth is seen as a business opportunity. The logic of market environmentalism also restricts the exploration of options to secure water resources for the region's future. Currently, there is a failure to address the substantial overexploitation of groundwater sources that the drinking water service relies upon, which jeopardizes both the population's fundamental right to water and the city's sustainability. The case of Aguascalientes, Mexico is significant because it represents not only the initial foray into private company involvement in providing drinking water services in this country, but it also stands as the first instance where the contractual term concluded. Consequently, local authorities opted for remunicipalizing the service to be administered by a public organization.